Repertoire of transcribed peripheral blood T-cell receptor beta chain variable-region genes in acute rheumatic fever. - Abbott, W G (1996)
Patients with severe group A streptococcal infections have abnormalities in the Vbeta repertoire of peripheral blood T cells that are consistent with superantigen stimulation by cytoplasmic membrane proteins. The purpose of this study was to determine whether similar changes in Vbeta repertoire could be found for patients with acute rheumatic fever (ARF). The mean Vbeta repertoire of peripheral blood T cells in nine hospitalized ARF patients was similar to that of 34 controls and did not change during 6 months of follow-up in 6 of the ARF subjects. We were unable to detect changes in the Vbeta repertoire of peripheral blood T cells from patients with ARF that could be attributed to the influence of a superantigen.